2017
DOI: 10.1155/2017/7594953
|View full text |Cite
|
Sign up to set email alerts
|

Breast Density and Breast Cancer Incidence in the Lebanese Population: Results from a Retrospective Multicenter Study

Abstract: Purpose To study the distribution of breast mammogram density in Lebanese women and correlate it with breast cancer (BC) incidence. Methods Data from 1,049 women who had screening or diagnostic mammography were retrospectively reviewed. Age, menopausal status, contraceptives or hormonal replacement therapy (HRT), parity, breastfeeding, history of BC, breast mammogram density, and final BI-RADS assessment were collected. Breast density was analyzed in each age category and compared according to factors that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
4
10
0
2
Order By: Relevance
“…In this study, the mean age of included patients with breast cancer metastasizing to bone was 52.5±14.2 years, identical to the mean age found by Salem et al among breast cancer patients in Lebanon [13].…”
Section: Clinicopathologic Variablessupporting
confidence: 88%
“…In this study, the mean age of included patients with breast cancer metastasizing to bone was 52.5±14.2 years, identical to the mean age found by Salem et al among breast cancer patients in Lebanon [13].…”
Section: Clinicopathologic Variablessupporting
confidence: 88%
“…Comparison in the percentage of females with breast density of 50% and above between our study's results and the studies performed in Lebanon [17] and New York [18]. …”
Section: Figurementioning
confidence: 58%
“…These results in Emirati women were compared with published results in Lebanese and Western women [17, 18] (Table 4, Figure 2). These studies also found a negative correlation between breast density and age.…”
Section: Resultsmentioning
confidence: 80%
“…The study demonstrated a significant inverse relationship between age and MBD among normal and breast cancer groups of Jordanian women. The results revealed that 68.9% of women in the normal and 70.9% of breast cancer group reported high MBD – ACR BI-RADS c or d. This is higher than the recorded percentage for women in the United States (55.4%), 17 China (52.8%), 22 Lebanon (52.9%), 23 Uganda (39%), 24 United Arab Emirates (23.6%), 25 and India (16%). 26 This density difference emphasises both the increased risk of breast cancer in this population and the importance of local data informing screening policy rather than that of the US or other international data.…”
Section: Discussionmentioning
confidence: 77%